BLOOD PRESSURE BALANCE IN CHRONIC KIDNEY DISEASE. (June 2018) - Mars, M.; Kammoun, K.; Guesmi, R.; Chaker, H.; Mahfoudh, H.; Chaabouni, Y.; Yaich, S.; Kharrat, M.; Hmida, M. Ben; Jarraya, F.; Hachicha, J.
Abstract : Objective: Hypertension is common in chronic kidney disease (CKD) and is a major determinant of CKD progression. Ambulatory blood pressure monitoring (ABPM) has been proposed as a better method to evaluate blood pressure (BP) in real life conditions. The objective of our study is to better specify the characteristics of ABPM in patients with CKD compared to the rest of the hypertensive population. Design and method: We conducted a retrospective study including all patients who benefited from an ABPM between January 2014 and Juin 2017. The CKD was established based on the definitions of KDIGO 2012. We divided our patients into 2 groups: G1: patients with ckd and G2: patients without CKD. The comparison between the 2 groups was carried out by Chi-square test and one factor ANOVA. Results: The study included 241 cases with a sex ratio of 0, 84. The prevalence of CKD was 81% including 33 % stage 2, 56 % stage 3; 10 % stage 4 and 1% stage 5. Patients with CKD were older (55 ± 16 years vs 42 ± 15 years; p < 0, 001). There were no significant difference regarding sex (p = 0, 07) and body mass index (p = 0, 06). The mean blood pressure (BP) in consultation was 157/85 (G1) and 145/ 86 (G2) (p = 0, 03; p = 0, 5). The indications of ABPM were different in the two groups: unbalanced hypertension (G1: 67%, G2: 37, 5%), borderline hypertension (G1: 13.4%, G2: 22, 5 % (G1: 1.7%, G2: 3%) and the search for masked hypertension (G1: 20%, 40%) with a significant difference (p = 0.002). In the ABPM, there was no difference in systolic and diastolic BP, whereas the difference was significant comparing patients having satges 4 and 5 CKD with other patients (149/82 vs 136 /78; p = 0, 016; p = 0, 3).The mean number of antihypertensive drugs was greater in the presence of CKD (1, 8 ± 1, 3 vs 0.8 ± 0, 9; p < 0.001). Conclusions: BP should be monitored closely in hypertensive patients with CKD. ABPM seems to be the appropriate method in detecting hypertension and monitoring adequacy of treatment in patients with CKD.